PEMBELAJARAN SAINS DENGAN METODE STEAM PADA ANAK USIA DINI - Adelia Salsabila Baiduri Syarif; Belananda; Inaya Tasya Wati; Nisa`el Amal (STPI Bina Insan Mulia Yogyakarta, 2023)
This research aims to find out how AUD science learning uses the STEAM method. STEAM-based learning can make children think critically, comprehensively, and stimulate children to be able to solve problems. STEAM is used to focus on understanding the integrated nature of the disciplines of science, technology, arts, and mathematics in children. The STEAM method greatly influences children's creativity. Creativity is an individual's way of building aspects of life to enjoy quality of life. Children's creativity will develop if it is well nurtured, but it will become a hidden talent if it is not stimulated. STEAM-based learning methods can be applied to increase children's science knowledge because this STEAM learning method aims to apply an active and creative learning model. This research method uses a literature study method (literature review) where this method focuses on investigation and critical analysis of existing literature or sources of information regarding a particular topic or issue.